(untitled) (Raparin Journal of Humanities (RJH), 2025)
Teacher leadership, a concept gaining prominence in educational discourse, denotes the active involvement of educators in influencing practices and policies within and beyond their individual classrooms. This study explores the multi-faceted nature of teacher leadership, specifically focusing on eliciting teachers’ perceptions, practices, and institutional conditions shaping Kurdish EFL teachers’ leadership in Kurdistan Region (KR) universities. To this end, the research adopts a mixed method research design using a questionnaire and a set of open-ended questions. The results of the questionnaire highlight a critical division in Kurdish EFL teachers’ practice of academic leadership. While Kurdish tertiary EFL teachers report a high degree of pedagogical freedom and self-efficacy at the individual level, they view their leadership power more negatively when it comes to participation in broader institutional governance. Furthermore, the open-ended questions revealed similar results. Teachers remain individually autonomous in their own teaching/research, but collectively marginalised in administration and governance. The findings provide actionable recommendations for policy makers and administrators to nurture a more inclusive, participatory, and a sustainable model of faculty empowerment and teacher leadership in the Kurdish context.